Increasing Interest and Motivation in Learning Through Al-Qur'an Hadith Subjects with Standard Strategies At Madrasah Aliyah Negeri (MAN) 1 Sintang - Murniyati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Education is an important aspect in character building and improving the quality of human resources. Al-Qur'an Hadith, is one of the subjects that has a significant role in character building. This is because this lesson aims to give students a deep understanding of Islamic teachings, strengthen their moral and spiritual values, and help them develop a good relationship with Allah and the society around them. However, recently a lot of students are less enthusiastic about learning in these subjects, of course one of the factors is the method used by teachers is less attractive, thus making students less enthusiastic in studying these subjects. One of the schools that experienced this was Madrasah Aliyah Negeri 1 Sintang, where the students there experienced degradation to study the Al-Qur'an Hadith subject. However, he managed to overcome this problem thanks to the strategy used by the Al-Qur'an Hadith teacher at Madrasah Aliyah Negeri 1 Sintang. So this study aims to find out the PAKEM strategy used by Al-Qur'an Hadith teachers in increasing interest and motivation in learning. This study used a descriptive research method, which aims to describe and interpret the object of research according to the conditions in the field. The results of the research show that the Madrasah Aliyah Negeri 1 Sintang school uses the PAKEM strategy for the Qur'an Hadith subject in a planning, active, contextual and fun way so that students are able to understand significantly so that this strategy is very effective in the teaching and learning process. In addition, teachers also engage in interesting and relevant activities for students to increase their learning interest. Activities that involve interaction, exploration, and creativity can make learning more fun and interesting for students.